KEBIJAKAN PENUNDAAN PERNIKAHAN SUAMI DALAM MASA IDAH ISTRI: STUDI IMPLEMENTASI DI KUA MASARAN DALAM PERSPEKTIF MAQĀṢID JASSER AUDA - Sindi Septiana; Suciyani (LPPM STAI Muhammadiyah Probolinggo, 2026)
The issuance of Circular Letter Number P-005/DJ.III/HK.00.7/10/2021 concerning Marriage during the Wife's Waiting Period has caused legal uncertainty due to inconsistent implementation in various Religious Affairs Offices (KUA). This study seeks to examine how the circular letter is implemented in the Masaran Subdistrict KUA and review it from the perspective of Jasser Auda's contemporary Maqāṣid al-syarī‘ah. This study uses a qualitative method with a legal-empirical orientation, in which data is obtained directly from the field through interviews, document reviews, and literature exploration. This study found that the Masaran Subdistrict KUA consistently implements this circular letter as an administrative guideline for marriage registration, even though it realizes that this policy has no legal binding force. From the perspective of Jasser Auda's Maqāṣid al-syarī‘ah, this implementation reflects an orientation towards purposefulness and efforts to maintain public interest, particularly in realizing administrative order and legal certainty in marriage. This research contributes theoretically to the development of contemporary maqāṣid studies in administrative law, as well as providing practical contributions to policymakers regarding the legitimacy of administrative policies within the framework of Islamic law.